2011
DOI: 10.1029/2011gl046843
|View full text |Cite
|
Sign up to set email alerts
|

The evolution of Titan's detached haze layer near equinox in 2009

Abstract: [1] Saturn's moon Titan has a massive atmosphere laden with layers of photochemical haze. We report a recent dramatic change in the vertical structure of this haze, with a persistent 'detached' layer dropping in altitude from over 500 km to only 380 km between 2007 and 2010. The detached haze layer appears to be a well-defined tracer for Titan's meridional stratospheric circulation, models of which suggest that a pole-to-pole meridional cell weakens during equinox as solar heating becomes more symmetric. These… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
58
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 53 publications
(74 citation statements)
references
References 21 publications
15
58
1
Order By: Relevance
“…Titan's atmosphere is photochemically active even at lower altitudes and leads to the formation of complex tholin-like potential prebiotic molecules due to the penetrating longer wavelength photons. This is consistent with observations of Titan's haze stretching between B500 km and B50 km above the surface 9 , containing several regions of haze (0, A, B and C) as recently characterized by the Cassini CIRS instrument 34,35 .…”
supporting
confidence: 92%
“…Titan's atmosphere is photochemically active even at lower altitudes and leads to the formation of complex tholin-like potential prebiotic molecules due to the penetrating longer wavelength photons. This is consistent with observations of Titan's haze stretching between B500 km and B50 km above the surface 9 , containing several regions of haze (0, A, B and C) as recently characterized by the Cassini CIRS instrument 34,35 .…”
supporting
confidence: 92%
“…Indeed, short-term variations observed during the Cassini mission can arise from changes in the circulation around the time of the equinox. The collapse of the detached aerosol layer (West et al 2011) suggests that the dynamics during this period go through a rapid transition which should also affect the gas distribution. The rapid decrease after mid-2009, for which the most straightforward explanation is that the vortex has shrunk somewhat, would be consistent with the weakening thermal gradient we find here and that of the winds also reported by Achterberg et al (2008Achterberg et al ( , 2011 and Teanby et al (2009b).…”
Section: Discussion Of the Results And Possible Interpretationsmentioning
confidence: 99%
“…These investigations have shown that a large-scale reversal occurred in the single pole-to-pole circulation affecting the distribution of the atmospheric structure after the northern equinox in mid-2009, with the gases in the summer hemisphere showing upwelling while in the winter pole a corresponding subsidence was found (Achterberg et al 2008(Achterberg et al , 2011Bampasidis et al 2012;Teanby et al 2012). Whereas until 2011 a significant build-up of trace gases, haze, and condensates was still observed over the north pole (West et al 2011(West et al , 2016Jennings et al 2012aJennings et al , 2012bCoustenis et al 2013;Vinatier et al 2015), toward the end of that period, the vortex and hotspot reported in Jennings et al (2015) and Achterberg et al (2008) had practically disappeared. In its place, similar features started to appear near the south pole, which have evolved to what we see today.In the absence of sunlight, gases that subsidize have accumulated since 2012 and become enhanced (e.g., Coustenis et al 2016 and references within;Teanby et al 2017), and a subset of those have been suggested to be causing the haze decrease found in the north and its subsequent increase in the south (Jennings et al 2012b(Jennings et al , 2015.…”
Section: Introductionmentioning
confidence: 96%